Improving Students’ Vocabulary by Using Show and Tell (S&T) Method at the First Grade Students of SMA Negeri 6 Toraja Utara - Sartika Manda; Ahmad Talib; Nur Aeni; Nur Aeni (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This research aims (1) to determine the level of students' vocabulary mastery before and after being taught using the S&T method (2) to find out whether using the S&T method further improves students' vocabulary. This is in accordance with the hypothesis which states that the use of the Show and Tell (S&T) method improve students' vocabulary. The design used in this study is a pre-experimental, which is One Group Pretest-Posttest design with the sample is from class X IPS 2, which consists of 16 students and using cluster random sampling technique. In obtaining the data, the researchers used the test as an instrument. The results of data analysis showed that by using the Show and Tell (S&T) method, students' vocabulary mastery improved. It can be proven by the t-test value of -27.547 which is less than the t-table value of 2.602, which means that H0 of this research was rejected and H1 was accepted. So, it can be concluded that the use of the Show and Tell (S&T) method improve students' vocabulary at the first-grade students of SMA Negeri 6 Toraja Utara.